REFORMULASI SANKSI PIDANA TERHADAP PENYALAHGUNA NARKOTIKA YANG BERASAL DARI KALANGAN ATAS - Ela Valentina Damanik; Erdianto Erdianto; Syaifullah Yophie Ardiyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Narcotics abuse is a complex problem and has a broad perspective, both in the fields ofmedical, psychosocial, mental and psychiatric services. At present, narcotics abusers can belikened to an iceberg that includes all levels of society, especially the upper class. Therefore, asan effort to deal with narcotics abusers who are increasing day by day and the need to create anew paradigm to renew the public's view of narcotics abusers, especially the upper class society,where the upper class society in its implementation is more privileged. Therefore, it is necessaryto reformulate criminal sanctions as stipulated in Law Number 35 of 2009 concerning Narcoticsto create laws that are more effective and fair in responding to modernization goals. The purposeof this study is to understand the regulation and application of criminal sanctions againstnarcotics abusers in Indonesia and to develop the idea of reformulation of appropriate sanctionsagainst narcotics abusers from the upper class society.The research conducted is normative legal research or known as doctrinal legal research,which uses data sourced from library research and literature quotations related to the issuesstudied. Therefore, the secondary legal sources used consist of secondary, primary and tertiarylegal materials as well as data from interviews in the form of primary data.In this research, the type of data analysis used is qualitative data analysis which isproduced in the form of descriptive data. From the elaboration of the discussion and researchconducted, several conclusions can be obtained, namely: First, narcotics addicts and narcoticsabusers as stipulated in Article 54 of Law Number 35 of 2009 concerning Narcotics states thatnarcotics addicts and narcotics abusers are required to undergo medical rehabilitation andsocial rehabilitation. However, in fact the implementation of rehabilitation is not evenlydistributed to all levels of society. Second, an increase in imprisonment and fines, as well as anincrease in treatment and/or treatment services in the form of medical rehabilitation and socialrehabilitation as an idea formulated by taking into account awareness, legal ideals, outlook onlife and philosophy originating from Pancasila and the Opening of the Constitution of theRepublic of Indonesia in 1945.Keywords: Reformulation – Criminal Sanctions – Rehabilitation